Seeing families as policy actors: exploring higher-order thinking reforms in Singapore through low-income families' perspectives - Chiong, Charleen; Lim, Leonel (Journal of education policy, 2022)
Empirical policy analyses have hitherto largely focused on how formal institutions and agents (such as schools and ministries) formulate and enact policy. Less considered is the role and perspectives of families in mediating education policy. This paper discusses the importance of viewing families as not only policy subjects, but policy actors who play important roles in negotiating education policy reform. In the Singapore context, as in many contexts, there has been a growing policy emphasis on developing higher-order critical and innovative thinking to equip young people for the global knowledge economy. However, it is at the socio-economic margins of society that policy ideals tend not to map out as policymakers expect. We draw on in-depth interviews with low-income families - analysed using a governmentality perspective - to understand how families navigate Singapore's policy landscape, particularly its growing emphasis on higher-order competencies within a neoliberal, performative, high-stakes education system. The paper concludes by elaborating on equity implications arising from this analysis.